2022
DOI: 10.3390/ijms232315015
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Model Using AAV9-Cre to Knockout Adult Leydig Cell Gene Expression Reveals a Physiological Role of Glucocorticoid Receptor Signalling in Leydig Cell Function

Abstract: Glucocorticoids are steroids involved in key physiological processes such as development, metabolism, inflammatory and stress responses and are mostly used exogenously as medications to treat various inflammation-based conditions. They act via the glucocorticoid receptor (GR) expressed in most cells. Exogenous glucocorticoids can negatively impact the function of the Leydig cells in the testis, leading to decreased androgen production. However, endogenous glucocorticoids are produced by the adrenal and within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Sertoli-specific Gr deletion in mice had a limited impact on fertility but did reduce Sertoli cell and spermatocyte numbers (Hazra et al, 2014). A 50% reduction of GR in Leydig cells using AAV9-Cre disrupted steroidogenesis (Gannon et al, 2022), suggesting a role for GR in Leydig cell function. Rat adrenalectomy studies showed decreased sperm counts were partially restored by dexamethasone, but not sperm morphology (Silva et al, 2014).…”
Section: Effects Of Loss Of Receptor Signalingmentioning
confidence: 99%
“…Sertoli-specific Gr deletion in mice had a limited impact on fertility but did reduce Sertoli cell and spermatocyte numbers (Hazra et al, 2014). A 50% reduction of GR in Leydig cells using AAV9-Cre disrupted steroidogenesis (Gannon et al, 2022), suggesting a role for GR in Leydig cell function. Rat adrenalectomy studies showed decreased sperm counts were partially restored by dexamethasone, but not sperm morphology (Silva et al, 2014).…”
Section: Effects Of Loss Of Receptor Signalingmentioning
confidence: 99%
“…Annalucia et al characterized the ability of viral vectors, including adenovirus, lentivirus, and adeno-associated virus (AAV), to deliver exogenous genes targeting Leydig cells in adult mouse testes and determined that AAV serotype 9 (AAV9) + neuraminidase transported the transgenes efficiently [142]. Moreover, AAV9-driven Cre was generated by the Diane group to delete endogenous glucocorticoid receptors in adult Leydig cells; the silencing efficiency of AAV9-Cre to AR was 48% 7 days after injection, which was higher than that of the Cyp17a1-iCre transgenic approach (28%) [143]. The AAV9 virus was found to infect germ cells of the testes from 3-week mice [144], possibly because these testes are not fully developed in immature mice, and the blood-testis barrier is not fully established.…”
Section: Cre Transgenic Mice For Sertoli and Leydig Cellsmentioning
confidence: 99%
“…Detectable GR expression has been described in several key testicular cell types, including the somatic Sertoli, Leydig, and peritubular cells, as well as early germ cell populations [ 10 - 12 ]. The specific role of GR within most of these cell types remains unknown.…”
Section: Introductionmentioning
confidence: 99%